Зміна концентрації солей у процесі регенерації іонообмінних фільтрів - Терновцев, В.О.; Зоря, О.В. (Екологічна безпека та природокористування, 2012)
The problems of changing the concentration of hardness ions in sodium chloride for regeneration of the sodium-cationite filters. Shows the relationship between stiffness and coefficient of regeneration solutions, as well as the effect of calcium and sodium in the regeneration process.